Factors Affecting Credit Growth of Vietnamese Commercial Banks - Thanh Tung Diep; Van Thuan Nguyen (ETIKONOMI, 2022)
This research analyzes the factors that affect the credit growthof the Vietnamese commercial banking system. This study usedata from the annual reports and financial statements of 16commercial banks listed on the HOSE, HNX, and UPCOMexchanges that have operated continuously from 2011 to 2020.Two linear regression models were employed with two dependentvariables: the credit growth rate and credit size. The findingsindicate that credit size in the previous period, the annualgrowth rate of capital mobilization, bank size, and return onassets (ROA) positively affect the credit growth of Vietnamesecommercial banks while liquidity ratio negatively affects them.Also, the bad debt ratio’s effect on credit growth is unclear. Hence,some suggestions and recommendations are given for commercialbanks to maintain stable, safe, and sustainable credit growth.JEL Classification: G21, E50, E52